Study of efficacy of oral ivermectin in comparison to commonly used topical antiscabetic drugs gamma benzene hexachloride and permethrin - Kanwar, Suman; Mathur, Sunil K.; Sankhla, Sanjay (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Scabies is an infectious disease, contagious in nature and caused by Sarcoptes Scabiei, is transmitted readily, often throughout an entire household, by prolonged skin-to-skin contact with an infected person. The objective was to know the efficacy of oral ivermectin in the treatment of scabies infection in comparison to commonly used topical antiscabetic drugs gamma benzene hexachloride and permethrin. Methods: Using prospective, longitudinal, comparative randomized design, study was conducted for a period of one year in 299 patients, in the age group of 5 to 60 years, belonging to both sexes, attending outpatient department of dermatology of J.L.N. Medical College and associated hospitals Ajmer (RAJ), India. Pregnant and lactating women, children below 5 years, elderly patients more than 60 year, patients not willing to come for follow-up and patients with any serious systemic illness were excluded. Data so collected, were analyzed as per the aims and objectives with the help of appropriate statistical software (primer statistical software version 6). Results: Efficacy of oral ivermectin therapy was comparable with topical permethrin therapy but more efficacious (statistically significant) than topical gama benzene hexachloride therapy. Conclusions: Ivermectin can be a very useful weapon in patients who do not show compliance with topical therapy.